ETIKA BISNIS DALAM AKAD MUDHẬRABAH (Studi di Baitul Maal wa at-Tamwil Tamzis Kantor Cabang Pembantu Bandung Ibu Inggit Garnasih) - Annisa Eka Rahayu (FASTABIQ: JURNAL STUDI ISLAM, 2020)
Baitul Maal wa at-Tamwil Tamzis Inggit Garnasih is a Sharia Cooperative that is very strategically located with Micro business in Kebon Kelapa ITC Market Bandung. That small capital deficit entrepreneurs can do mudharabah financing at Tamzis. The number of small entrepreneurs who do the financing Tamzis needs to be careful in running his business. Considering that the mudhârabah contract is a contract of cooperation between Shahibul Mal and Mudharib, both must hold to full trust, it is necessary to implement Islamic ethics in carrying out the contract. The purpose of this study was to eximine the susccesful implementation of business ethics in mudharabah contracts at BMT TAMZIS KCP Bandung Inggit Garnasih. The research method is based on a sociological juridical approach. Research methods conducted based on the normative juridical approach. This research is understood as filed research, which is collecting documentation data that is located in BMT TAMZIS KCP Bandung Inggit Garnasih.The research used is analytical descriptive, that is, research to describe current problems or based on reality in the field, and the type of data used in this research, namely primary data, material or data and secondary data in the form of supporting books. related to the object. The results showed that the Islamic business ethics carried out in the mudharabah contract at BMT TAMZIS KCP Bandung Inggit Garnasih showed an example of its success in helping members (customers) who are traders in the Kebon Kalapa ITC market enivironment.Keywords: BMT, Islamic Business Ethics, and Mudharabah.